Discordant Association of C‐Reactive Protein With Clinical Events and Coronary Luminal Narrowing in Postmenopausal Women: Data From the Women's Angiographic Vitamin and Estrogen (WAVE) Study. Issue 9 (10th June 2013) - Patel, Dhavalkumar; Jhamnani, Sunny; Ahmad, Soha; Silverman, Angela; Lindsay, Joseph
Abstract Background The incidence of cardiovascular events had been shown to be associated with C‐reactive protein (CRP). However, it is unclear that the cardiovascular risk associated with CRP is due to progressive coronary narrowing or to other factors such as formation of unstable plaque. This study was designed to determine the effect of baseline CRP on cardiovascular events and on the progression of atherosclerotic narrowing among 423 postmenopausal women with angiographic stenosis between 15% and 75%. Hypothesis Baseline CRP levels may affect cardiovascular events and progression of atherosclerotic coronary artery narrowing among postmenopausal women. Methods Baseline and follow‐up (2.8 years) angiographic data were analyzed among 320 women. Women were stratified into 4 quartiles according to baseline CRP levels. The changes in lumen diameter and clinical events in each quartile were compared. Results The annualized changes in minimal and average lumen diameter in diseased and nondiseased coronary segments were not significantly associated with baseline CRP levels. The composite end point of all‐cause mortality and myocardial infarction (MI) increased from 3% (3/107) in the first CRP quartile to 14% (14/98) in fourth CRP quartile (P < 0.001). Similar results were found for cardiovascular death and MI (increased from 1% (2/107) in the first quartile to 11% (11/98) in fourth quartile). The difference remained significant even after adjustment for baseline differences and cardiovascular risk factors. Conclusions Higher baseline CRP was associated with increased risk of clinical events but was not associated with annualized change in luminal diameters. Thus, increased risk of adverse events among patients with higher baseline CRP events was independent of progression of atherosclerosis as measured by change in minimal or average luminal diameter.